2012
DOI: 10.3139/146.110718
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion and elastic properties of mullite-type Bi2Ga4O9 and Bi2Fe4O9 single crystals

Abstract: Resonant ultrasound spectroscopy was used to characterize the elastic properties of single crystal orthorhombic Bi 2 Ga 4 O 9 and Bi 2 Fe 4 O 9 between room temperature and about 1 200 K. Additionally, the coefficients of thermal expansion were studied in the range 100 K to 1 280 K using high-resolution dilatometry and X-ray powder diffraction. for Bi 2 Fe 4 O 9 .I n both mullite-type compounds the strong bond chains built up by edge-sharing coordination octahedra extending parallel to [001] dominate the aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Alike mullite, the thermal expansion behavior violates the empirical rule (the lowest thermal expansion occurs to the elastically stiffest crystal direction). This discrepancy was explained in terms of pure geometric considerations [27][28][29], however, the underlying microscopic reason is still unclear. The phonon density of states (PDOS) and its partial components from each atom in the asymmetric unit (Bi, Al, O) are shown in Fig.…”
Section: X-ray Diffraction and Thermal Expansionmentioning
confidence: 78%
See 1 more Smart Citation
“…Alike mullite, the thermal expansion behavior violates the empirical rule (the lowest thermal expansion occurs to the elastically stiffest crystal direction). This discrepancy was explained in terms of pure geometric considerations [27][28][29], however, the underlying microscopic reason is still unclear. The phonon density of states (PDOS) and its partial components from each atom in the asymmetric unit (Bi, Al, O) are shown in Fig.…”
Section: X-ray Diffraction and Thermal Expansionmentioning
confidence: 78%
“…3; almost similar behaviors of the corresponding ones in Bi 2 Ga 4 O 9 [25]. For a comparison, the axial bulk moduli for Bi 2 Ga 4 O 9 (K a ¼230.4(4)GPa, K b ¼309.5(5) and K c ¼446(2)GPa, in the crystallographic a-b-and c-direction) and Bi 2 Fe 4 O 9 (K a ¼ 163.6(1)GPa, K b ¼303.8(5)GPa and K c ¼ 431.6(1)GPa) were calculated [26] from the observed elastic constants [27,28]. López-de-la-Torre et al [29] observed the similar trend for Bi 2 Al 4 O 9 and Bi 2 Mn 4 O 10 compounds, showing that the linear incompressibities of these isotypic materials follow the order as K c 4K b 4K a .…”
Section: X-ray Diffraction and Thermal Expansionmentioning
confidence: 99%
“…However, a comprehensive study of mullite-type Bi 2 M 4 O 9 (M = Al, Ga, Fe) showed that in these compounds the polarized LEP is important for the stabilisation of the crystal structure (see [13], and references therein). On the other hand, the elastically soft LEP leads to a distinct reduction of their mean elastic stiffness [14].…”
Section: Introductionmentioning
confidence: 98%
“…The structure analysis shows that the mullite-type structures are characterized by one dimensional chains of edge sharing MO 6 octahedra, and M 2 O 7 double tetrahedral units and BiO 6 E groups (where E refers to a 6s 2 lone electron pair) interconnect the octahedral chains in an alternating ordered manner along the caxis [4]. From the perspective of application, the phase should be stable up to a temperature of about 1200 K without showing any phase transition or decomposition.…”
Section: Introductionmentioning
confidence: 98%
“…Gesing et al have systematically investigated the thermal expansion, stability, and elasticity properties in (Bi 1 À x Sr x ) 2 (M 1 1 À y M 2 y ) 4 O 9 À x and Bi 2 M 4 O 9 (M¼Al 3 þ , Ga 3 þ , and Fe 3 þ ). [5][6][7][8] Additionally, the extensive formation of Bi 2 M 1 4 O 9 -Bi 2 M 2 4 O 9 solid solutions provides an additional feature for the magnetic, electrical, and other materials properties which often depend on the distribution of M 1 and M 2 cations on the available octahedral and tetrahedral sites, and Weber et al have used 57 Fe Mössbauer spectroscopy of Bi 2 (Fe x M 1 À x ) 4 O 9 (M ¼Al 3 þ , Ga 3 þ ) to investigate the distribution of Fe 3 þ and Al 3 þ /Ga 3 þ in the octahedral and tetrahedral sites [9,10].…”
Section: Introductionmentioning
confidence: 98%